Platform diffusion at temporary gatherings: Social coordination and ecosystem emergence - Fang, Tommy Pan; Wu, Andy; Clough, David R. (Strategic Management Journal, 2021)
Abstract Research Summary Software platforms create value by cultivating an ecosystem of complementary products and services. Existing explanations for how a prospective complementor chooses platforms to join assume the complementor has rich information about the range of available platforms. However, complementors lack this information in many ecosystems, raising the question of how complementors learn about platforms in the first place. We investigate whether attending a temporary gathering—a hackathon—impacts the platform choices of software developers. Through a large‐scale quantitative study of 1,302 developers and 167 hackathons, supported by qualitative research, we analyze the multiple channels—sponsorship, social learning, knowledge exchange, and social coordination—through which hackathons serve as a social forum for the diffusion of platform adoption among attendees. Managerial Summary A software platform such as Windows, iOS, or Amazon Web Services relies on third‐party developers to create applications that complement the platform and make it valuable for end users. However, developers face a wide range of possible platforms, and they may have limited information about which platforms would be worthwhile to develop for. A software platform business can educate and encourage developers to adopt their platform by supporting in‐person software development competitions, known as hackathons. Developers learn about prospective platforms that advertise at the hackathon. Developers also learn whether and how to use a platform by observing and teaching one other. Hackathons are particularly useful for spreading platform technologies: developers prefer to adopt widely used platforms, and hackathons permit developers to identify and join fashionable platforms.